2020
DOI: 10.1186/s40478-020-01067-5
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability in the prediction of pituitary neuroendocrine tumors prognosis

Abstract: The purpose of this study was to analyze the impact of copy number variations (CNV) on sporadic pituitary neuroendocrine tumors (PitNETs) prognosis, to identify specific prognosis markers according to the known clinico-pathological classification. CGH array analysis was performed on 195 fresh-frozen PitNETs (56 gonadotroph, 11 immunonegative, 56 somatotroph, 39 lactotroph and 33 corticotroph), with 5 years post-surgery follow-up (124 recurrences), classified according to the five-tiered grading classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
0
20
1
Order By: Relevance
“…The quantity of chromosomal alterations was reported to be associated with invasion in a cohort of 27 pediatric Cushing's disease subjects, 45 and with macroadenomas, silent or Crooke's cell tumors, in another recent study on 22 patients 33 . In our study on 33 cortricotroph tumors, a higher level of CNVs seemed to be associated with macroadenomas, without reaching statistical significance, but was not associated with invasion, with silent tumors, nor with USP8 mutations 44 . Overall, we also failed to find an association between tumor recurrence at 5 years and the quantity of CNVs.…”
Section: Molecular Prognostic Factorscontrasting
confidence: 60%
“…The quantity of chromosomal alterations was reported to be associated with invasion in a cohort of 27 pediatric Cushing's disease subjects, 45 and with macroadenomas, silent or Crooke's cell tumors, in another recent study on 22 patients 33 . In our study on 33 cortricotroph tumors, a higher level of CNVs seemed to be associated with macroadenomas, without reaching statistical significance, but was not associated with invasion, with silent tumors, nor with USP8 mutations 44 . Overall, we also failed to find an association between tumor recurrence at 5 years and the quantity of CNVs.…”
Section: Molecular Prognostic Factorscontrasting
confidence: 60%
“…The development of the carcinogenesis process is usually correlated with the abnormalities of chromosomes that mainly result from frequent mutations in genes that contribute in preserving the stability of the chromosomes ( Huang and Zhou, 2021 ). Those mutations evoke genomic instability events that can support tumor progression and further enhance metastasis ( Lasolle et al, 2020 ). Additionally, other rearrangements and/or deletions have been detected in tumor suppressor genes, and the substitution single base has been detected in cancer cell clones with multiple mutations that can activate oncogenes ( e.g ., MYC and RAS) and inhibit tumor suppressor genes such as TP53 ( Ma et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ability to accurately identify molecular signatures associated with histopathology and clinical outcomes is still not possible. Although a study of Lasolle et al did show that the quantity of copy number variations is dependent on tumor type (higher in prolactinomas) compared to other tumors, another study showed that all functional pituitary tumors demonstrated higher variability in copy-number profiles (Bi et al, 2017;Lasolle et al, 2020). As for aggressive and malignant pituitary tumors lactotroph tumors are the second most frequent after corticotrophinomas (McCormack et al, 2018).…”
Section: Genomic Profile Of Pituitary Tumorsmentioning
confidence: 99%